Forms and Techniques of Learning Outcomes Evaluation at MTs Al Ishlahiyah Binjai - Jannah, Nurul; Nabilah, Nada; Kristiana, Kristiana; Azzubair, Muhammad; Sitepu, Rama Dhania Br (Holistic Science, 2024)
This research was conducted to examine the steps and techniques for evaluating Islamic Religious Education learning outcomes. The research is qualitative in nature by analyzing several literature books and as the main data source. The results of the research are the steps for evaluating learning outcomes, namely, preparing a plan for evaluating learning outcomes, collecting data, verifying data, processing and analyzing data, providing interpretations and drawing conclusions, and then continuing with the evaluation results. Meanwhile, learning outcomes evaluation techniques are test techniques, objective techniques and non-test techniques. The research results state that the diagnostic assessment aims to diagnose students' basic abilities and determine students' initial conditions. Diagnostic assessments are divided into non-cognitive diagnostic assessments and cognitive diagnostic assessments. The Merdeka Belajar curriculum wants to create a happy learning atmosphere.